Characterization of SOD and GPX Gene Families in the Soybeans in Response to Drought and Salinity Stresses - Muqadas Aleem; Saba Aleem; Iram Sharif; Zhiyi Wu; Maida Aleem; Ammara Tahir; Rana Muhammad Atif; Hafiza Masooma Naseer Cheema; Amir Shakeel; Sun Lei; Deyue Yu; Hui Wang; et al. (MDPI AG, 2022)
Plant stresses causing accumulation of reactive oxidative species (ROS) are scavenged by effective antioxidant defense systems. Therefore, the present study performed genome-wide identification of superoxide dismutase (SOD) and glutathione peroxidase (GPX) gene families in cultivated and wild soybeans, and 11 other legume species. We identified a total of 101 and 95 genes of SOD and GPX, respectively, across thirteen legume species. The highest numbers of SODs and GPXs were identified in cultivated (Glycine max) and wild (Glycine soja). A comparative phylogenetic study revealed highest homology among the SODs and GPXs of cultivated and wild soybeans relative to other legumes. The exon/intron structure, motif and synteny blocks were conserved in both soybean species. According to Ka/Ks, purifying the selection played the major evolutionary role in these gene families, and segmental duplication are major driving force for SODs and GPXs expansion. In addition, the qRT-PCR analysis of the G. max and G. soja SOD and GPX genes revealed significant differential expression of these genes in response to oxidative, drought and salinity stresses in root tissue. In conclusion, our study provides new insights for the evolution of SOD and GPX gene families in legumes, and provides resources for further functional characterization of these genes for multiple stresses.